New formyl-peptides, as stimulator of non-specific organism resistance against mycobacteria - Pohorila, M; Martynov, A; Romanova, O; Sidorenko, T; Igumnova, N; Yukhimenko, V; Shcherbak, O (Annals of Mechnikov's Institute, 2020)
Introduction. The key element in the formation of tuberculosis infection (TI) is the inability of alveolar macrophage to complete phagocytosis of mycobacteria absorbed by them, that caused by both features of the pathogens biology and the tissue macrophages. It is known, that M. tuberculosis is capable long-term persistence and proliferation in alveolar macrophage cytoplasm because of high stability of them cell walls to the lysosomal enzymes action. Mainly, the phenomenon of granulomatous reaction, inherent of tuberculosis (TB), reflects the inadequacy in elimination of tuberculosis pathogen of alveolar macrophages. Thus, the inclusion of agents that can activate completed phagocytosis of mycobacteria by alveolar macrophages, in the base of anti-TB therapy is a promising direction in the prevention of latent tuberculosis reactivation. Materials and Method. The ability of formyl-peptides activate the completeness of mycobacteria phagocytosis by alveolar macrophages absorbed by them were evaluated in vitro. For reaching the aim of the study we had used a broncho-alveolar lavage obtained by white laboratory male mice 2 months of age. As a comparison drug we used the officinal preparation "Liasten". To determine the lysosomal activity by the presence of peroxidase was treated with acridine orange causing selective staining red lysosomes. Acid phosphatase activity was studied using azocoupling reaction for staining granules in the cytoplasm blue or purple. Results are expressed as mean cytochemical coefficient (LZC). Results and discussion. Incubation of alveolar macrophages and formyl-peptides leads to a significant increase the index of mycobacteria phagocytosis completeness for vaccine strains - (1,70 ± 0,31) and (1,20 ± 0,22), respectively, (p <0.05). The standard medication - Liasten - also increased the "killing" ability of tissue macrophages compared to control: (1,8 ± 0,25) and (1,20 ± 0,22), respectively, (p <0.05). Lysosomal activity of alveolar macrophages exposed formyl-peptides significantly increased in comparison with the control - (97,80 ± 5,1) and (80,9 ± 4,3) acridine orange-positive cells, respectively, (p <0.05). However, the effect of formyl-peptides on lysosomal activity of macrophages did not exceed the reference drug action - (97,80 ± 5,1) and (95,72 ± 5,3) acridine orange-positive cells, respectively, without significant differences. Incubation with formyl-peptides resulted in a significant increase of LZC of acid phosphatase in macrophages - (2,08 ± 0,20) and (1,59 ± 0,14), respectively, (p <0.05). Significant differences between the content of this enzyme in macrophages when exposed formyl-peptides and the reference drug were not detected. Conclusion. As a result the co-incubation of alveolar macrophages and new formil-peptides activates BCG phagocytosis completeness. Also, there is the influence of the studied substances under significant lysosomal activity and increase the content of acid phosphatase in macrophages isolated from broncho-alveolar lavage in comparison with the control. The level of functional activity stimulation of phagocytes under the influence of formyl-peptide is the same, that we registered after the Liasten administration. It has indicating prospects of the medicinal preparation creation on the formyl-peptides basis, which stimulates the organism non-specific resistance.